The silence within: a conserved intragenic silencing element governs HTLV-1 expression via host RUNX1 complex binding - Natasha Jansz; Damian F. J. Purcell (npj Viruses)
A defining feature of Human T-cell leukaemia virus type 1 (HTLV-1) infection is the establishment of reversible latency that can persist for many years. This latency enables the expansion of infected CD4+ T cells, ultimately contributing to adult T-cell leukaemia (ATL) and inflammatory disease. Sugata et al. identify a viral negative regulatory element within the HTLV-1 proviral genome that governs transcriptional latency. This intragenic silencing element contains binding sites for the master haematopoietic transcription factor, RUNX1. RUNX1 complex binding represses viral expression, thereby reducing viral production, antigen presentation, and susceptibility to cytotoxic T lymphocyte responses. The intragenic silencing element described in their study is unique to HTLV-1 and represents a novel strategy by which the virus achieves lifelong persistence in the host.